Stosunek elektoratu do radiowych reklam wyborczych - Łukasik-Turecka, Agnieszka (Political Preferences, 2014)
The surveys conducted in the autumn of 2013 show that most of those surveyed pay no attention to election advertisements aired on the radio. The greatest percentage of persons not interested in radio election advertisements are followers of the Left Democratic Alliance (Sojusz Lewicy Demokratycznej, SLD) - 74.4%. An equally large percentage of people who are not interested in radio election advertising was reported among those polled who declared they would not vote if the election for the Sejm was held next Sunday - 74%. Followers of the Your Movement [Twój Ruch] coalition and supporters of other parties than those named above also pay little atten- tion to radio election advertising - in both categories this percentage is 68.4% each. Out of the Civic Platform [Platforma Obywatelska, PO] supporters as many as 67.3 % of those surveyed are not interested in radio election advertisements, while among the Law and Justice [Prawo i Sprawiedliwość, PiS] followers the percentage of those not interested in election advertisements on the radio is 65.8%. The lowest percentage (although also exceeding 60%) of people not paying attention to radio election advertisements was reported among supporters of the Polish People's Party [Polskie Stronnictwo Ludowe, PSL] - 64%.Taking into account the results of surveys concerning ideological views, the highest percentage of persons not interested in radio election advertisements are those surveyed who define their views as left-wing - 76.7%. A slightly smaller percentage of persons not interested in radio election advertisements was reported among those surveyed who defined their views as centrist - 71.6%, while the percentage of those surveyed defining their views as right-wing and not interested in this type of advertising was 65.8%. Out of those who find it difficult to define their views the percentage of people not interested in radio election advertisements is 67.3%.The survey results also show that election advertisements aired on the radio do not have any effect on the voting decisions of the majority of those surveyed. This form of political communication has the smallest influence on the Democratic Left Alliance supporters - as many as 80 % of those polled and declaring themselves as followers of this party believe that radio election advertising has no effect on their voting decisions. The percentage of persons who believe that election advertisements on the radio do not influence their voting decisions is also high in the case of the other categories of those surveyed. In the case of the supporters of other parties than those mentioned, this percentage is 79.8%; for those who would not vote if the election was held on the nearest Sunday - 78,7%, while for the PO, PSL, PiS and Your Movement supporters: 77.8%, 72.1%, 71.4% and 73.6% respectively.In the case of the survey results regarding ideological views, the highest percentage of those surveyed who believe that radio election advertisements do not have any impact on their voting decisions was reported among persons who define their views as centrist - 82.2%, and not much lower among those defining their views as left-wing - 81.7%. The smallest percentage of those who believe that radio election advertisements do not influence their voting decisions was reported among the persons defining their views as right-wing- 74.6% and among those who find it difficult to define their views - 72.2%.